Insights into CSF-1/CSF-1R signaling: the role of macrophage in radiotherapy - Shang, Qingchao; Zhang, Pei; Lei, Xiao; Du, Lehui; Qu, Baolin (Frontiers in Immunology, 2025)
Macrophage plays an important role in homeostasis and immunity, and dysfunctional macrophage polarization is believed to be associated with the pathogenesis of tissue fibrosis and tumor progression. Colony stimulating factor-1 (CSF-1), a polypeptide chain cytokine, through its receptor (CSF-1R) regulates the differentiation of macrophages. Recently, the promising therapeutic potential of CSF-1/CSF-1R signaling pathway inhibition in cancer treatment is widely used. Furthermore, inhibition of CSF-1/CSF-1R signaling combined with radiotherapy has been extensively studied to reduce immunosuppression and promote abscopal effect. In addition, cumulative evidence demonstrated that M2 phenotype macrophage is dominant in tissue fibrosis and the inhibition of CSF-1/CSF-1R signaling pathway ameliorated pulmonary fibrosis, including radiation-induced lung fibrosis. Herein, we provide a comprehensive review of the CSF-1/CSF-1R signaling pathway in radiotherapy, with a focus on advances in macrophage-targeted strategies in the treatment of cancer and pulmonary fibrosis.